KILL NOT YOUR CHILDREN ON A PLEA OF WANT... - Karim, Rukhsana; Rabia Kareem (Journal of Postgraduate Medical Institute, 2022)
“Kill not your children for fear of want. We shall provide sustenance for them as well as for you. Verily the killing of them is a great sin.”1 Unintended pregnancies are a significant public and social health problem throughout the world and majority of these end up in an induced abortion.2 This is definitely a wake-up call for the stakeholders worldwide as this proportion is on a constant rise.3 According to a latest statistic, nearly half of all pregnancies are unintended, which in its own self, is a global crisis. Out of these, 60% end up in induced abortion and 45% of these abortions take place with unsafe techniques or in unsafe circumstances, contributing substantially to the maternal morbidity, leading to 5-13% of all maternal deaths, which represents a global failure to uphold basic human rights.4 Out of these 45% unsafe abortions, 97% take place in developing countries, like Pakistan.4 According to the available literature, the proportion of unintended pregnancies in Pakistan increased from 38% to 46% in a decade’s time. The national abortion rate, however, is 50/1000 women and in one year and 623,000 women have been treated for post-abortion complications.5 The increase in the proportion of unintended pregnancies can be attributed mainly to lack of awareness and access to the contraceptive practices, as the contraceptive prevalence is low in Pakistan.6,7 In addition to this, various other factors are implicated including the desired family size, socioeconomic factors, and availability of appropriate healthcare services.8,9 This is why, in developing countries like Pakistan, majority of women seeking induced abortion due to unintended pregnancies are married, older, and have high parity as compared to the developed countries where more than half of the women seeking induced abortion were unmarried and young.10,11 In countries, like Pakistan, it is very difficult to obtain reliable data on induced abortion because most of these take place behind the closed doors due to laws and eventual penalties, according to Pakistan Penal Code.12 The majority of the statistics, related to induced abortion, are derived indirectly from the health facilities where patients having post-abortion complications are managed. These complications can range from sepsis, uterine perforation, injury to the urinary bladder and gut, renal failure and hysterectomy. But this is just the tip of the iceberg, as every woman is not lucky enough to reach a health care facility and there are chances that they end up in unreported long term morbidity, or even mortality. In addition, unsafe abortion, a preventable cause of maternal morbidity and mortality, has long term sequelae in the form of sub-fertility, psychological disturbances and socioeconomic consequence.5,8 In order to avoid the short and long term consequences, we need to have a multipronged approach to improve and expand the provision of healthcare services to reduce the incidence and complications associated with induced abortion, mostly carried out unlawfully.11 Educating men about different contraceptive methods available, can save women from unsafe abortions. At the same time, religious scholars must be involved in creating awareness in people regarding the sanctity of human life. Policy makers and community leaders have to empower women to make decisions about family planning and contraception.4 Last but not the least, it is high time to help women avert unintended pregnancies ending up in induced abortions by educating, supporting and expanding the family planning services. This will not only help in the reduction of maternal morbidity and mortality associated with these but will also curtail the associated costs to the families, communities and the society as a whole.12